THE ROLE AND IMPORTANCE OF AN INTEGRATED APPROACH IN THE ORGANIZATION OF EDUCATION (SCIENCE TIME JOURNAL, 2025)
This article is about the importance and role of integrative approaches in education. The role of integrative approaches in the organization of education is incomparable. Integration is important for a simple and detailed explanation of the educational material to the learner. Usually, we rely on the conceptual idea that the result of the integration of academic subjects is the acquisition of subjective new knowledge, which is not formed when subjects are taught without interdependence. The process of interdisciplinary synthesis of new knowledge in the educational process is very slow, sometimes covering a period equal to several decades. During the learning process, the teacher will have to lead the student to subjective new knowledge based on previously acquired knowledge in various subjects during one or several lessons, even for a few minutes. That is, appropriate conditions should be created not for transfer of knowledge in a ready state, but for their synthesis. It is not an exaggeration to say that one of the technological methods of implementing this task is related to the transfer of knowledge from one field to another, which is the main mechanism for establishing interdisciplinary relations. It is impossible to ensure interdisciplinary communication with the student. with integrated education without personal understanding of philosophical issues. Unintelligible integration brings the process of cognition in the student's mind to an abstract state and through it to a confused conclusion.